Respuesta :

Answer:

The equation has one solution.

A value of x that makes the equation true is -3, which when substituted into the equation and simplified makes the equation turn into 18=18.

A value of x that makes the equation false is 0, which when substituted into the equation and simplified makes the equation turn into 0=18.

Step-by-step explanation:

Hope this helped! :)

Answer:

Step-by-step explanation:

The equation has one solution conditional equation

-6x = 18

-6x/-6 = 18/-6

x = -3

A value of x that makes the equation true is -3, which when substituted into the equation and simplified makes the equation turn into 18 = 18

-6x = 18

-6(-3) = 18

18 =18

A value of x that makes the equation false is 3, which when substituded into the equation and simplified makes the equation turn into -18 = 18

-6x = 18

--6(3) = 18

-18 = 18